King of envy - Huang, Ana (Huang, Ana. Kings of sin series, 2025)
"Dangerous. Powerful. Reclusive. Vuk Markovic is notorious for shunning human interactions. The scarred billionaire rarely talks, andhe has no interest in relationships outside his small but trusted circle. His only exception? Her. The beauty to his beast, the object of his obsession. He saw her first. He wanted her first. But now, she's engaged to his oldest friend--and the closer the wedding looms, the more he's torn between loyalty and desire. She should be his...and he might just risk it all to have her...Beautiful. Successful. Glamorous. To the world, supermodel Ayana Kidane leads the perfect life. Her career has skyrocketed, and she's engaged to one of New York's most eligible bachelors. What people don't know is that the engagement is only a business arrangement. He gets his inheritance when they marry; she gets the money she needs to leave her abusive agency. Pretending to be in love should be easy--until she finds herself increasingly drawn to her fiancâe's enigmatic best man. Vuk thrills andterrifies her in equal measure. She knows she should stay away, butwhen her wedding is thrown into chaos, he's the only person who makes her feel safe...Until his past catches up with them and threatenseverything they love"--